2018
DOI: 10.2196/11247
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver-Focused, Web-Based Interventions: Systematic Review and Meta-Analysis (Part 2)

Abstract: BackgroundApproaches to support the health and well-being of family caregivers of adults with chronic conditions are increasingly important given the key roles caregivers play in helping family members to live in the community. Web-based interventions to support caregivers have the potential to lessen the negative health impacts associated with caregiving and result in improved health outcomes.ObjectiveThe primary objective of this systematic review and meta-analysis was to examine the effect of caregiver-focu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 50 publications
1
72
0
8
Order By: Relevance
“…The caregiving responsibilities and associated caregiving-related strain experienced by a sizeable proportion of our faculty population present ample opportunity for collaboration between human resource o ces, wellness programs, and faculty development o ces to address current and future employee caregiving-work con icts and responsibilities. Many of our institutions already offer a variety of resources and there are myriad programs in the community; for example: respite care; sitter/companion programs; home health/visiting nurses; meal preparation; shopping services; chore/task services; nancial planning; caregiver-focused web-based interventions [22]; and online/virtual support groups (e.g., Facebook, Instagram, Twitter). However, there is little evidence documenting the utilization and impact of these programs on faculty outcome measures, such as well-being and burnout or institutional outcomes, such as recruitment, retention, faculty satisfaction, promotion, or retirement.…”
Section: Discussionmentioning
confidence: 99%
“…The caregiving responsibilities and associated caregiving-related strain experienced by a sizeable proportion of our faculty population present ample opportunity for collaboration between human resource o ces, wellness programs, and faculty development o ces to address current and future employee caregiving-work con icts and responsibilities. Many of our institutions already offer a variety of resources and there are myriad programs in the community; for example: respite care; sitter/companion programs; home health/visiting nurses; meal preparation; shopping services; chore/task services; nancial planning; caregiver-focused web-based interventions [22]; and online/virtual support groups (e.g., Facebook, Instagram, Twitter). However, there is little evidence documenting the utilization and impact of these programs on faculty outcome measures, such as well-being and burnout or institutional outcomes, such as recruitment, retention, faculty satisfaction, promotion, or retirement.…”
Section: Discussionmentioning
confidence: 99%
“…The reviews all conclude that content, structure and duration differ markedly between the reported interventions, which included various designs; online support groups, informational websites, websites combined with telephone support or email support, and websites combined with exchange with other caregivers online. Altogether, the reviews report a range of improved family caregiver outcomes, such as increased knowledge, self-efficacy, self-esteem, coping skills, wellbeing and reduced anxiety, depression, stress, strain, and burden [26]. Overall, the reviews conclude that web-based family caregiver interventions can be beneficial in offering information and support, but more research is needed.…”
Section: Introductionmentioning
confidence: 95%
“…The use of web-based interventions to support family caregivers has increased lately. A total of 12 systematic literature reviews [26][27][28][29][30][31][32][33][34][35][36][37] report on various web-based interventions, half of them focusing on family caregivers of patients diagnosed with dementia, and the others focusing on caregivers of patients affected by cancer or chronic conditions. The reviews all conclude that content, structure and duration differ markedly between the reported interventions, which included various designs; online support groups, informational websites, websites combined with telephone support or email support, and websites combined with exchange with other caregivers online.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7Various systematic reviews suggest that web-based interventions may result in a range of improved health outcomes for caregivers, including reductions in depression, stress, distress and anxiety. (8)(9)(10)(11) Other studies have identi ed that greater public education is needed for caregivers, and improved mechanisms are needed for busy clinicians to provide caregiver education. (12) We developed iGeriCare (www.igericare.ca), a multimodal e-learning intervention to help educate family caregivers of people with dementia.…”
Section: Introductionmentioning
confidence: 99%